Thermal response to sequential tropical cyclone passages: Statistic analysis and idealized experiments - He, Shunzhi; Cheng, Xiaoping; Fei, Jianfang; Li, Xiangcheng; Wei, Zexun; Huang, Xiaogang (Frontiers in Earth Science, 2023)
The cold wake caused by a tropical cyclone (TC) extends for hundreds of kilometers and persists for several weeks, thus influencing the surface response for any subsequent TCs that might pass over it. It is commonly accepted that sea-surface temperature (SST) cooling, as produced by a single TC, occurs primarily through vertical mixing. However, when there are sequential TCs, the earlier TC can dramatically change the thermal structure of the upper ocean, which may influence the subsequent development of a latter TC (LTC). Therefore, the contribution of horizontal advection and vertical mixing to SST-cooling during the passage of LTCs is of great interest. Using observations and numerical simulations,, the SST change during the passage of LTC was investigated. The results demonstrated that, on average, the SST cooling caused by LTC shows an overall decreasing trend with enhanced lingering wakes. Budget analysis of the model simulations suggests that an earlier TC can suppress the vertical mixing induced by LTC mainly through an alteration of dynamics within the deepened mixed layer and the contribution of the vertical mixing to the SST cooling is weaker due to the intensification of the earlier TC. The weakened vertical mixing dominated the decrease in SST cooling induced by the latter TC. In contrast, the cold wake generated by the earlier TC can produce more cold water on the right side of the TC’s track, which contributes to stronger horizontal advection upon the arrival of LTC. In general, the effects of the earlier TC can suppress the sea-surface thermal response to LTC. If the contribution of the horizontal advection to SST cooling is neglected, the SST cooling induced by the latter TC could be reduced by more than 40%. As for the response of the sub-surface water to the passage of an LTC, the weakened warm anomaly induced the vertical mixing and the enhanced cooling anomaly caused by the vertical advection explain the reduced tendency for the mixed layer to deepen. These results highlight the importance of optimally depicting cold wake in the numerical simulation to improve the prediction of the upper ocean responses to sequential TCs.